Insulin-like growth factors and aging: lessons from Laron syndrome - Werner, Haim; Laron, Zvi (Frontiers in Endocrinology, 2023)
The growth hormone (GH)-insulin-like growth factor-1 (IGF1) signaling pathway emerged in recent years as a key determinant of aging and longevity. Disruption of this network in different animal species, including flies, nematodes and mouse, was consistently associated with an extended lifespan. Epidemiological analyses have shown that patients with Laron syndrome (LS), the best-characterized disease under the umbrella of the congenital IGF1 deficiencies, seem to be protected from cancer. While aging and cancer, as a rule, are considered diametrically opposite processes, modern lines of evidence reinforce the notion that aging and cancer might, as a matter of fact, be regarded as divergent manifestations of identical biochemical and cellular underlying processes. While the effect of individual mutations on lifespan and healthspan are very difficult to assess, genome-wide screenings identified a number of differentially represented aging-and longevity-associated genes in patients with LS.The present review summarizes recent data that emerged from comprehensive analyses of LS patients and portrays a number of previously unrecognized targets for GH-IGF1 action. Our article sheds light on complex aging and longevity processes, with a particular emphasis on the role of the GH-IGF1 network in these mechanisms.